Performance of Permanent Magnet Synchronous Generator (pmsg) 3 Phase Radial Flux Results Modification of Induction Motor - Ahmad Raafi Fauzi; Rama Arya Sobhita; Anggara Trisna Nugraha; Anisa Fitri Santosa (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
Abstract: The demand for electrical energy in Indonesia has experienced a significant surge, becoming indispensable for nearly all modern activities. However, despite this surge, the primary energy source for power plants continues to heavily rely on fossil fuels. Consequently, it is imperative to transition towards renewable energy sources to mitigate environmental impact and tackle the prevailing energy crisis. In response to this need, permanent magnet synchronous generators have emerged as a promising alternative within the electricity industry. These generators operate by utilizing permanent magnets to generate a magnetic field within the coil, thereby eliminating the necessity for excitation current. By leveraging renewable energy sources such as wind or hydro power, these generators strive to optimize electricity production and alleviate the ongoing energy crisis. This research project aims to repurpose materials sourced from used water pump motors, including rotors and stators, to construct permanent magnet synchronous generators. The process involves incorporating permanent magnets into the rotor and modifying the original motor winding. Through rigorous testing involving the application of a 40 Ohm load and varying rotational speeds between 2000 and 1600 rpm, the research reveals that the generator can generate a minimum power output of 0.7 Watts at 200 rpm and a maximum power output of 41.8 Watts at 1600 rpm. The optimal efficiency of 75.78% is attained at 400 rpm. Overall, this research underscores the potential of repurposing existing materials to develop renewable energy solutions, offering a sustainable approach to addressing not only the energy needs of Indonesia but also those of other regions globally.